Hypochromic red cells as a prognostic indicator of survival among patients with systemic sclerosis screened for pulmonary hypertension - Xanthouli, Panagiota; Gordjani, Ojan; Benjamin, Nicola; Harutyunova, Satenik; Egenlauf, Benjamin; Marra, Alberto M.; Haas, Simon; Milde, Nicklas; Blank, Norbert; Lorenz, Hanns-Martin; Fiehn, Christoph; Ulrich, Silvia; et al. (Arthritis Research & Therapy, 2023)
Patients with systemic sclerosis (SSc) are frequently affected by iron deficiency, particularly those with pulmonary hypertension (PH). The first data indicate the prognostic importance of hypochromic red cells (% HRC) > 2% among patients with PH. Hence, the objective of our study was to investigate the prognostic value of % HRC in SSc patients screened for PH.
Gesehen am 05.12.2023